Deformation and fracture studies in aluminium alloys - Dowling, J (1975)
The research is concerned with the problem of embrittlement in fully aged alloys of the H.30 type (Al-Mg-Si). These alloys fracture in a brittle intergranular fashion at low strains but when small amounts of manganese (~ 0.5wt%) are added, intergranular failure is suppressed and the ductility of the alloys is increased. Previous work performed by Messrs. Alcan International Limited has shown that the manganese-bearing alloys contain incoherent intermetallic particles of the α(Al12Mn3Si) phase. The particles have a diameter of ~ 0.1μm and are rod-shaped. It was considered that these particles might be responsible for the improved mechanical behaviour of the manganese bearing alloys, but the mechanism involved was not known. Earlier work by the author has indicated that the manganese-bearing particles can modify the surface slip line distribution and it was suggested that this effect of slip hornogenization might prevent intergranular failure. The present work investigates the extent to which these 0.1μm particles influence the nucleation and propagation of fracture and explores the mechanisms involved. Three Al-Mg-Si alloys were selected - BD3(Al-0.58wt%Mg - 1.02wt%Si), BD6(Al-0.58wt%Mg - 0.99wt%Si - 0.21wt%Mn) and BD8(Al-0.57wt%Mg - 0.95wt%Si - 0.50wt%Mn). After casting, the alloys were thermo-mechanically processed into sheet form before solution heat treatment at 560°C and artificial ageing at 185°C. The alloy microstructures were examined using optical and transmission electron microscopy. The grain size of the alloys were measured and the dispersion parameters of 0.1μm a phase particles were determined. These measurements show that the grain size of the brittle alloy BD3 is ~ 400μm while that of BD6 and BD8 is ~ 100μm. When fully aged, three alloys contain a fine ageing precipitate of Mg2Si, grain boundary precipitates and precipitate free zones adjacent to the grain boundaries. The manganese bearing alloys additionally contain the 0.1μm α(Al12Mn3Si) phase particles and also coarser, 5μm particles of the same phase. An investigation of the precipitation kinetics of α(Al12Mn3Si) particles from a chill cast alloy was made, and also attempts were made to increase the grain size of BD8. It is shown that above 530°C, the a phase particles grow very quickly. Below 530°C, their growth is slower, but the kinetics are complicated by the onset of precipitation of Mg2Si phase particles which coarsen rapidly. The subsequent grain growth experiments indicate that both these precipitate phases are effective in inhibiting extensive grain growth in the manganese-bearing alloys. Within the scope of the present research, it was thus not possible to produce comparable grain sizes in BD3, BD6 and BD8 and to compare their mechanical properties at constant grain size. The mechanical properties of the three alloys were studied using compression tests and tensile tests and their deformation structures were examined using both optical and electron microscopy. In compression, BD3 can withstand larger strains before fracture than in tensile deformation. This enables an analysis of its structure after plastic deformation to be made. It is found that at compressive strains up to 9%, BD3 contains well defined slip bands and these can produce distortion at the grain boundaries. At low compressive strains, BD6 and BD8 also contain slip bands but these are closer together and their spacing decreases with increasing strain; eventually, the deformation structure consists of homogeneous arrays of dislocations. No local grain boundary distortion was observed in BD6 or BD8. It is concluded that the slip bands produce stress concentrations at the grain boundaries. In BD3, these are large because (a) the grain size is large and (b) the slip band width is narrow. It is proposed that intergranular decohesion occurs at small tensile strains, Because the stress concentrations are large enough to nucleate voids at the grain boundary precipitates and fracture proceeds by coalescence of these voids. This is supported by scanning electron microscopy of fracture surfaces at room temperature; the grain boundary surfaces are covered with fine dimples whose size corresponds to the observed spacing of the grain boundary precipitates. It is also concluded that intergranular decohesion in BD6 and BD8 is suppressed at low strains because the stress concentrations at the head of the slip bands are reduced by (a) the smaller grain size and (b) the broadening of the slip band width by the 0.1μm α phase particles. Tensile tests at 20°C, 150°C and 185°C show that the fracture processes in BD6 and BD8 are controlled by the presence of both the coarse, ~ 5μm α phase particles and the 0.1μm particles. The coarse, ~ 5μm, particles nucleate voids shortly after yield and the coarsening of these voids determines the start of localised plastic deformation. Fracture does not occur at the U.T.S., but only after large amounts of localised plastic deformation. Scanning and transmission electron microscopy indicate that in these alloys, fracture takes place when voids are formed at the 0.1μm particles and the voids coalesce. It is proposed that this void formation requires conditions of high stress and strain such that void formation and coalescence occur virtually simultaneously. The difficulty of void formation at these particles is related to the high matrix-particle binding energy and the particle shape. Because of these latter properties, the 0.1μm particles inhibit the spread of voids formed at the coarse particles and so fracture is delayed until a very late stage of deformation. In conclusion, it is proposed that the 0.1μm particles in the manganese-bearing alloys are important in controlling the deformation mechanisms. Not only do these particles disperse slip, thus preventing intergranular failure at low strains, but they also appear to be effective in impeding crack propagation. Their efficacy in both these processes depends on their dispersion parameters, shape and binding energy with the matrix. These parameters are discussed in relation to the production of an alloy with optimum mechanical properties.